OPTIMASI DESAIN FASAD KACA DAN RUANG DALAM TERHADAP PENCAHAYAAN ALAMI PADA KEGIATAN BELAJAR MENGAJAR DI RUANG KELAS UNIVERSITAS MUHAMMADIYAH, BANDUNG - Fahrany, Farrah; Punama, Mimie (Riset Arsitektur (RISA), 2024)
Abstract - Indonesia is located in a tropical climate that receives much natural light from the reflection of sunlight. This abundant natural light can be used as an illumination in buildings and can save energy, especially in educational buildings such as Muhammadiyah University, Bandung is a building with an educational function where the facade uses glass on its sides with a function of space in it, namely classrooms. The classroom at the Muhammadiyah University Bandung Building has two class unit models with differences in the design of openings, resulting in strong differences in natural light in the two classroom models, there are rooms covered by 2 large-dimensional glass openings facing East, West, North, South. And then there's a classroom with openings facing south where the dimension of the openings is quite small. This study will be conducted in the form of a building exhibiting evaluation, how the glass facade and classroom enclosing elements in buildings affect the quantity and quality of natural lighting. Simulation results will be examined and design optimizations will be performed on glass facades and classroom enclosing elements with various architectural element configurations. The method used is quantitative with an experimental-simulation approach. The model of the building will be created with the SketchUp application and will then be simulated by Velux Daylight Visualizer Simulations were performed first to both existing classroom models. Results from the simulations show that there are problems in the quality and quantity of natural lighting in both classroom unit models that do not meet the standard. The design optimization of architectural elements is carried out to solve the problems of natural light quality including illumination and DF, and natural light quantities include lightness and glare contrast ratio. Class 1 units made furniture color modifications, opening modifications, light shelter additions, and incorporated all modifications. Class 2 units were glass modifications, furniture color modifications, and overall modifications. The optimization results show that the color modification of the fixing furniture has not reached the light quality standard and that the fixing has reached the light quantification standard of both classroom models. The modification of the opening dimension in the 1st class fixing unit has not reached the standard of light quality, and a slight fix to the fixing has not reached the standard of light quantification. The addition of light shelf to the class 1 unit model does not improve the quality of light and worsens to slightly improve the quantity of light. The glass modification in the 2nd class unit deteriorates the quality of light and does not improve the quantity of light. The incorporation of all modifications can improve the quality and quantity of light of both class unit models. . Keywords: quality, quantity of natural lighting, glass facade, design interior, classroom.